Multifunctional SERS Chip for Biological Application Realized by Double Fano Resonance - Weile Zhu; Huiyang Wang; Yuheng Wang; Shengde Liu; Jianglei Di; Liyun Zhong (Nanomaterials)
The in situ and label-free detection of molecular information in biological cells has always been a challenging problem due to the weak Raman signal of biological molecules. The use of various resonance nanostructures has significantly advanced Surface-enhanced Raman spectroscopy (SERS) in signal enhancement in recent years. However, biological cells are often immersed in different formulations of culture medium with varying refractive indexes and are highly sensitive to the temperature of the microenvironment. This necessitates that SERS meets the requirements of refractive index insensitivity, low thermal damage, broadband enhancement, and other needs in addition to signal enhancement. Here, we propose a SERS chip with integrated dual Fano resonance and the corresponding analytical model. This model can be used to quickly lock the parameters and then analyze the performance of the dual resonance SERS chip. The simulation and experimental characterization results demonstrate that the integrated dual Fano resonances have the ability for independent broadband tuning. This capability enhances both the excitation and radiation processes of Raman signals simultaneously, ensuring that the resonance at the excitation wavelength is not affected by the culture medium (the refractive index) and reduces heat generation. Furthermore, the dual Fano resonance modes can synergize with each other to greatly enhance both the amplitude and enhanced range of the Raman signal, providing a stable, reliable, and comprehensive detection tool and strategy for fingerprint signal detection of bioactive samples.